INFORMATION TECHNOLOGIES IN EDUCATION - Kazimova Nafisaxon Minovarovna; Adildjonovoy Muzifabonu Abbasxon kizi (Scholar Express Journals, 2022)
This article discusses the introduction of information technology in education, one of the ways to improve their content is the possibility of independent learning for students, the creation of the necessary conditions for the formation and development of information sources of education, as well as technical and technological aspects.
Keywords: Information and communication technologies; information and educational resources; multimedia materials; portal technologies